HEMOGLOBIN STATUS OF FEMALE MEDICOS IN URBAN AREA AND FACTORS AFFECTING IT: AN OBSERVATIONAL CROSS-SECTIONAL STUDY - KALYANPUR, VARSHA; UDAYKUMAR, PADMAJA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objectives: Estimating the hemoglobin (Hb) status in female medicos through prospective cross-sectional study and assessment of influencing of cofactors were objectives. Methods: Women medicos who volunteered, consented and met selection criteria were enrolled. Hb level was estimated to diagnose anemia. Relationship with influencing factors was assessed statistically. Result: A total of 100 eligible students were enrolled. Mean age±standard deviation (SD) age of the participants' was 20.9±3.1 years (17-25 years). Mean±SD Hb was 12.25±1.0189 g% (9.0-16.0 g%). 33 were anemic, and mild anemia (32%) was frequent. There was a history of worm infestation in three students (3%), who were treated adequately. Nine were on iron supplements of which five were still anemic and were continuing the treatment by the end of the study. 28 (84.84%) anemic students were not on any iron or hematinic treatment. There was no association between the anemia and nature of diet, consumption of green leafy vegetables, consumption of coffee/tea after food, smoking/tobacco or alcohol consumption, mother's education, socioeconomic status, menstrual factors, and physical exercise. The prevalence of anemia was found to be higher in underweight and overweight students in comparison to students with normal body mass index.Asymptomatic participants (n=78) outnumbered symptomatic ones (n=22), but without any statistical significance. Easy fatigability (14%), pallor (7%), breathlessness (6%), weakness (9%), and easy bruising (1%) were frequent complaints. Conclusion: Anemia is frequent among women medicos, often underdiagnosed, under-reported, many remaining asymptomatic. Negligence of medical students toward their anemic status despite the awareness of consequences of low Hb level is a serious cause of concern. Keywords: Awareness, Hemoglobin, Nutritional anemia, Women medical students.